Opportunity and Motivation in the Selection of Part-Time Job as Food Delivery Service Provider during Covid-19: โอกาสและแรงจูงใจในการเลือกอาชีพเสริมผู้ให้บริการรับส่งอาหารเดลิเวอรีช่วงโควิด 19 - Plubplueng, Thitima; Plubplueng, Piyapong (Journal of Applied Economics and Management Strategy, 2021)
บทคัดย่อ บทความนี้นำเสนอมุมมองการเลือกอาชีพหลักและอาชีพเสริมของบุคคล โดยมีวัตถุประสงค์เพื่อศึกษาความน่าจะเป็นของการตัดสินใจและแรงจูงใจในการเลือกอาชีพผู้ให้บริการรับส่งอาหารเดลิเวอรีผ่าน แอปพลิเคชัน โดยใช้แนวคิดทุนมนุษย์ในการวิเคราะห์ข้อมูลเชิงปริมาณจากแบบสอบถามด้วยสมการถดถอย โลจิสติก กำหนดให้ประชากรเป็นผู้ให้บริการส่งอาหารเดลิเวอรี และสุ่มตัวอย่างแบบหลายขั้นตอน จำนวน 383 คน พบว่า อายุ บริษัทผู้ให้บริการ (แพลตฟอร์ม) ความพึงพอใจของลูกค้า และแรงจูงใจในการทำงาน มีผลต่อโอกาสในการตัดสินใจเลือกอาชีพผู้ให้บริการรับส่งอาหารเดลิเวอรีเป็นอาชีพเสริมซึ่งแรงจูงใจที่สำคัญที่สุด คือ ผลตอบแทนสูง โดยในกลุ่มบุคคลที่เลือกเป็นอาชีพหลักจะมีแรงจูงใจในการทำงานและความพึงพอใจของลูกค้าสูงกว่าบุคคลที่เลือกเป็นอาชีพเสริม ส่วนการวิจัยเชิงคุณภาพใช้แบบสัมภาษณ์มีโครงสร้างและวิเคราะห์เนื้อหาเชิงลึก โดยกำหนดกลุ่มเป้าหมายเป็นนักศึกษามหาวิทยาลัยเทคโนโลยีราชมงคลรัตนโกสินทร์ จำนวน 20 คน พบว่านักศึกษาส่วนใหญ่ทำเป็นอาชีพเสริม เนื่องจากได้รับค่าตอบแทนสูง มีความยืดหยุ่นและอิสระในการทำงาน อีกทั้งในช่วงเกิดสถานการณ์โรคระบาดไวรัสโควิด 19 เป็นช่วงเวลาและโอกาสที่ได้รับค่าตอบแทนสูงขณะที่มีการเรียนออนไลน์ด้วย ทั้งนี้นักศึกษาจะต้องจัดเวลาเรียนและทำงานให้สมดุลและเหมาะสมสำหรับบุคคลทั่วไปจำเป็นต้องเรียนรู้เงื่อนไขของผลตอบแทน ข้อจำกัด และเทคนิคการทำงานของแต่ละแอปพลิเคชันก่อนตัดสินใจเลือกเป็นอาชีพหลักหรืออาชีพเสริม ABSTRACT This research presented individuals’ perspectives on main and supplementary occupation selection. It aimed to study possible outcomes of decision-making and motivations behind the decision to work as food delivery drivers of mobile applications. The research applied the concept of human capital to the quantity analysis and logistic regression analysis of questionnaires. The population of the research was food delivery drivers, of which 383 samples were selected by multi-stage sampling. It was found that age, service providing companies (platforms), customer satisfaction and work motivation affected the population’s decision to be food delivery drivers as their supplementary occupation. The most important motivation was high remuneration. As for the population choosing to be food delivery drivers as their main occupation, work motivation and customer satisfaction affected their decision more than the population choosing to be food delivery drivers as their supplementary occupation. As for the part of qualitative research, the methodology was structured and in-depth interview. The target group was 20 students of Rajamangala University of Technology Rattanakosin. It was found that most students worked as food delivery drivers as their supplementary occupation due to high remuneration, work flexibility and adaptability. In addition, during the COVID-19 pandemic the remuneration was especially high and they were free to work, as the classes were offered online. However, they had to properly manage the balanced study and work times. Persons need to know the remuneration conditions, work restrictions and work techniques of each mobile application, before deciding to be a food delivery driver either as their main or supplementary occupation.